Species of Odontia and Tomentella (Thelephorales, Basidiomycota) new to Dagestan, Russia - Yu. Yu. Ivanushenko; S. V. Volobuev (Юг России: экология, развитие)
Aim. To obtain new data on the species diversity, phylogenetic structure, and ecological characteristics of thelephoroid fungi (Thelephorales, Basidiomycota) in the Republic of Dagestan.Material and Methods. Both micromorphological and molecular analyses were used for studying of the fungal specimens collected by the authors in 2018-2019 in the Gunibsky and Magaramkentsky Districts of Dagestan. Additional specimens from the Mycological Herbarium of the Komarov Botanical Institute of the Russian Academy of Sciences (LE) were studied. The ITS region of nrDNA was amplified with two pairs of primers, ITS1F/ITS4 and ITS5/ITS4.Results. Sixteen ITS sequences belonging to eight species were obtained from the studied material. Of them, 14 sequences clustered in the Tomentella clade and two sequences nested within the Odontia clade. Four species – Odontia duemmeri, Tomentella lapida, T. radiosa, T. terrestris – were registered for the first time for Dagestan. Detailed information on the specimens studied is presented. Species identification of Odontia fibrosa, Tomentella badia, T. ferruginea, and T. stuposa was confirmed by ITS nrDNA analysis.Conclusion. Data on the species richness of the genera Odontia and Tomentella in Dagestan is updated, and the species T. lilacinogrisea is excluded from the regional funga. To date the genera Odontia and Tomentella in the Republic of Dagestan are represented by three and fifteen species, respectively.